Algeria Economic Update : Building Resilience in Favorable Times - World Bank (Washington, DC, 2022)
This Algeria Economic Update provides an account of main recent economic developments and policies. It places them in a global and longer-term context and assesses the consequences of these developments and policy changes for Algeria’s prospects. The report is intended for a wide audience, including policymakers, business leaders, financial market participants, and the community of analysts and professionals working in and on Algeria. The report is organized into two chapters. Chapter 1 presents macroeconomic developments in Algeria up to late 2021 and early 2022. Chapter 2 describes the short- and medium-term outlook for the Algerian economy.